2016
DOI: 10.5527/wjn.v5.i4.308
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of membranoproliferative glomerulonephritis: Identification of a new GN: C3GN

Abstract: This review revises the reclassification of the membranoproliferative glomerulonephritis (MPGN) after the consensus conference that by 2015 reclassified all the glomerulonephritis basing on etiology and pathogenesis, instead of the histomorphological aspects. After reclassification, two types of MPGN are to date recognized: The immunocomplexes mediated MPGN and the complement mediated MPGN. The latter type is more extensively described in the review either because several of these entities are completely new o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 126 publications
(117 reference statements)
0
23
0
Order By: Relevance
“…The activation of immune complexes by the CP led to the assumption that other complement pathways are not involved in the disease pathogenesis. However, glomerular co-deposition of CFHR5, CFH, and FP has been found in MPGN I, LN and IgAN cases, indicating the AP involvement in these diseases [7,8,32,110,111]. In MPGN I patients, Servais et al reported low AP proteins levels, such as C3, CFB, CFH, and CFI (in 46.3, 34.1, 4.9, and 7.3% of cases, respectively) and the prevalence of the C3NeF (in 53.6% cases), what suggested the AP activation [62].…”
Section: Immune-complex Glomerulonephritismentioning
confidence: 99%
“…The activation of immune complexes by the CP led to the assumption that other complement pathways are not involved in the disease pathogenesis. However, glomerular co-deposition of CFHR5, CFH, and FP has been found in MPGN I, LN and IgAN cases, indicating the AP involvement in these diseases [7,8,32,110,111]. In MPGN I patients, Servais et al reported low AP proteins levels, such as C3, CFB, CFH, and CFI (in 46.3, 34.1, 4.9, and 7.3% of cases, respectively) and the prevalence of the C3NeF (in 53.6% cases), what suggested the AP activation [62].…”
Section: Immune-complex Glomerulonephritismentioning
confidence: 99%
“…Similarly, the role of complement in C3G has been better defined[9], thus allowing us to move from a histologically based classification of the MPGNs to a new classification based on pathophysiology[10,11]. …”
Section: Role Of Complement In Kidney Diseasesmentioning
confidence: 99%
“…The latter have clear signs of C3 staining with little or no immunoglobulin deposition evident on renal biopsy. C3Gs are further divided into dense deposit diseases (DDD) and the recently recognized entity C3GN[11]. …”
Section: Role Of Complement In Kidney Diseasesmentioning
confidence: 99%
See 2 more Smart Citations